SERVICES APPLICATION PROGRAMS USE A STATIC FILE IN THE NATIONAL ARCHIVES INDONESIAN REPUBLIC - Siti Wirdayatih; Ire Puspa Wardhani, Skom, MMSi (Jurnal Sistem Informasi, 2001)
With this program design is expected to be much help employees who are directlyinvolved with the activities associated with service usage. And design of this programis not intended to eliminate all manual work, but only to reduce human involvementin doing the work also reduces errors recurring nature committed against a job thatdemands accuracy.